What nonpharmacologic interventions are effective for reducing needle‐related procedural pain in children and adolescents?. Issue 2 (February 2015) - Dakoji, Srikanth; Satre, Thomas
Abstract : Evidence‐Based Answer : Distraction techniques and hypnosis reduce needlerelated pain among children and adolescents (SOR: A, meta‐analysis of RCTs). Breathing exercises, cognitive‐behavioral interventions, seated positioning, and stroking the skin before and during an immunization injection may also reduce pain (SOR: B, meta‐analysis of low‐quality RCTs).